Molecular Engineering to Access Fluorescent Trackers of Organelles by Cyclization: Chemical Environment of Nitrogen Atom‐Modulated Targets. (23rd August 2020) - Ma, Weixin; Zhang, Luoqiang; Shi, Yang; Ran, You; Liu, Yang; You, Jingsong
Abstract: In the application of new fluorescent bioimaging reagents, typically, one synthetic method yields one type of organelle tracker. Herein, a molecular engineering approach to access fluorescent trackers of multiple organelles via a powerful synthetic toolbox is described. Starting from easily available acridone and analogues, a one‐pot strategy is set up for the synthesis of structurally diversified heteroatom‐doped polycyclic aromatic hydrocarbons (PAHs, types I–V) through the rhodium‐catalyzed oxidative [4 + 2] cyclization of C = X (X = N, O, S) bonds with alkynes, which assembles both ionic and neutral fluorescent frameworks. The tetracyclic acridine‐type luminogens (I–IV) are capable of targeting multiple organelles, including lysosome, endoplasmic reticulum, mitochondria, and mitochondria‐nucleus, in which the chemical environments of the nitrogen atom modulate the targeting regions. The fluorescent organelle trackers developed herein possess unique features. The formally protonated type I molecules are suitable for the long‐term detection of the lysosomes (>24 h). The type IV molecules exhibit the photo‐induced transfer from mitochondria to nucleus targeting, which indicates that IV can be used as an effective tool for real‐time research on physiological processes related to cell trafficking. Abstract : A molecular engineering approach to access fluorescent trackers of multiple organelles through the rhodium‐catalyzed oxidative [4 + 2] cyclization of C = X (X = N, O, S) bonds with alkynes using easily available acridone and analogues is presented. The chemical environments of the nitrogen atom modulate the targeting regions in living cell imaging.